Nutritional value, in vitro gas production and in situ rumen degradation of maize silage enriched with Saccharomyces cerevisiae - Aragadvay-Yungán, Ramon (2022)
The aim of this study was to assess the nutritional value of maize silage (EMz) enriched with Saccharomyces cerevisiae (Sc) and quantify in vitro gas production and rumen degradation in situ. The treatments were T0: EMz, T1: EMz + 10% Sc, T2: EMz + 20% Sc. The content of neutral detergent fiber (NDF) and acid detergent fiber (ADF) showed a linear decreasing trend with respect to the increase in Sc levels and it was lower in T1 and T2 compared to T0. The digestibility of organic matter and metabolizable energy (ME) showed a linear downward trend as Sc levels were added. The lowest in vitro gas production corresponded to T1 (118.75 ml gas/0.5 g FDM). The greater amount of soluble fraction degraded in situ was evidenced in T2 (328.12 g/kg MS), also showing an increasing linear trend with the addition of Sc. It is concluded that the enrichment with 20% of Sc in the elaboration of EMz showed a lower production of gas in vitro and favored the parameters the rumen degradation in situ.